ANALISIS PERAMALAN PENJUALAN USAHA ARDYLA BAKERY DI MUARA BULIAN - Muryati Muryati (Universitas Batanghari Jambi, 2017)
The role of forecasting was very important for a company to run their business economy, especially to planning their production. The forecasting method used was expected to assist companies in determining the level of production in accordance with consumer demand in the future. The aim of this research was to know the sales forecasting of Ardila Bakery in Muara Bulian and to choose the correct forecasting method for sales forecasting in the future so it can become a reference to make a marketing startegy planning of Ardila Bakery in Muara Bulian. Methods used were Single Moving Averages, Exponential Smoothing, Weighted Moving Avareges, Exponential Trends and Exponential Trends and data used was sales data from June 2015 to May 2016. Based on the results of data collection then the sales data pattern of Ardila Bakery using 4 months Single Moving Averages Method with sales forecast was 458, MAD was 24.06 and MSE was 1,107.81. Six months Single Moving Averages Method with sales forecast was 462, MAD was to 26,95 and MSE was 1,297,97. Exponential Smoothing Method with alpha 0.1 with sales forecast was 466, MAD was 25,99 and MSE was 1,328,05. Exponential Smoothing Method with alpha 0.2 with sales forecast was 457, MAD was 26,33 and MSE was 1,359,64. Exponential Smoothing Method with alpha 0.5 with Sales Forecast was 437, MAD was 30.94 and MSE was 1,560.03. Weighted Moving Averages Method with weighted 3 with sales forecast was 435, MAD was 33.52 and MSE was 1,797.87. The Projected Trend Method with Sales Forecast was 446, MAD was 23.21 and MSE was 1.048.25 and Exponential Trend Method with Sales Forecast was 444, MAD was 461.08 and MSE was 213,707.47. Appropriate and good methods to apply to Ardila Bakery in Muara Bulian for bread products in June 2015 to May 2016 was Trend Projection Method, because it has smaller error rate than 4 months single moving averages method, 6 months single moving average, exponential smoothing with alpha (α = 0.1, α = 0.2 and α = 0.5), weighted moving average and exponential trend.Keywords: Single Moving Average, Double Moving Average, Single Exponential Smoothing